Deletion of low molecular weight protein tyrosine phosphatase (Acp1) protects against stress‐induced cardiomyopathy. Issue 4 (1st September 2015) - Wade, Fallou; Quijada, Pearl; Al‐Haffar, Kamar Mohamed Adib; Awad, Salma Mahmoud; Kunhi, Muhammad; Toko, Haruhiro; Marashly, Qussay; Belhaj, Karim; Zahid, Israa; Al‐Mohanna, Falah; Stanford, Stephanie M; Alvarez, Roberto; et al.
Abstract: The low molecular weight protein tyrosine phosphatase (LMPTP), encoded by the ACP1 gene, is a ubiquitously expressed phosphatase whose in vivo function in the heart and in cardiac diseases remains unknown. To investigate the in vivo role of LMPTP in cardiac function, we generated mice with genetic inactivation of the Acp1 locus and studied their response to long‐term pressure overload. Acp1 −/− mice develop normally and ageing mice do not show pathology in major tissues under basal conditions. However, Acp1 −/− mice are strikingly resistant to pressure overload hypertrophy and heart failure. Lmptp expression is high in the embryonic mouse heart, decreased in the postnatal stage, and increased in the adult mouse failing heart. We also show that LMPTP expression increases in end‐stage heart failure in humans. Consistent with their protected phenotype, Acp1 −/− mice subjected to pressure overload hypertrophy have attenuated fibrosis and decreased expression of fibrotic genes. Transcriptional profiling and analysis of molecular signalling show that the resistance of Acp1 −/− mice to pathological cardiac stress correlates with marginal re‐expression of fetal cardiac genes, increased insulin receptor beta phosphorylation, as well as PKA and ephrin receptor expression, and inactivation of the CaMKIIδ pathway. Our data show that ablation of Lmptp inhibits pathological cardiac remodelling and suggest that inhibition of LMPTP may be of therapeutic relevance for the treatment of human heart failure. © 2015 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.